2017
DOI: 10.1186/s12866-017-0926-5
|View full text |Cite
|
Sign up to set email alerts
|

Do biofilm communities respond to the chemical signatures of fracking? A test involving streams in North-central Arkansas

Abstract: BackgroundUnconventional natural gas (UNG) extraction (fracking) is ongoing in 29 North American shale basins (20 states), with ~6000 wells found within the Fayetteville shale (north-central Arkansas). If the chemical signature of fracking is detectable in streams, it can be employed to bookmark potential impacts. We evaluated benthic biofilm community composition as a proxy for stream chemistry so as to segregate anthropogenic signatures in eight Arkansas River catchments. In doing so, we tested the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…There were no significant differences in alpha diversity (Chao1, Heip’s evenness, observed, and PD whole tree) between UOG+ and UOG- streams assessed in this study, which is consistent with Johnson et al (2017) , in which there was no association between alpha diversity (Chao1, observed, Shannon evenness, and Shannon Entropy) and proximity to hydraulic fracturing activity. Trexler et al (2014) observed a significant reduction in alpha diversity (Chao1, Heip’s evenness, observed, and PD whole tree) and pH in streams near Marcellus shale activity (UOG development).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There were no significant differences in alpha diversity (Chao1, Heip’s evenness, observed, and PD whole tree) between UOG+ and UOG- streams assessed in this study, which is consistent with Johnson et al (2017) , in which there was no association between alpha diversity (Chao1, observed, Shannon evenness, and Shannon Entropy) and proximity to hydraulic fracturing activity. Trexler et al (2014) observed a significant reduction in alpha diversity (Chao1, Heip’s evenness, observed, and PD whole tree) and pH in streams near Marcellus shale activity (UOG development).…”
Section: Discussionsupporting
confidence: 87%
“…Recent work has found streams near hydraulic fracturing experience drastic shifts in certain bacterial assemblages (Acetobacteraceae, Methylocystaceae, and Phenylobacterium ) and had lower observed bacterial diversity ( Trexler et al, 2014 ). However, a study done in the Fayetteville shale formation did not find any significant difference in alpha diversity based on proximity to hydraulic fracturing, but it too noted an increased abundance of specific taxa ( Microcystis and Synechoccophycideae) in streams near hydraulic fracturing operations ( Johnson et al, 2017 ). Furthermore, that study noted little work has been done on evaluating the impact of hydraulic fracturing on streams.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multiple shared taxa between our two networks [i.e., Spartobacteria unclassified (Verrucomicrobia), Micrococcaceae (Actinobacteria), and Chitinophagaceae (Bacteroidetes)] increased in abundance under P additions. The abundance of taxa within these families may track the availability of P in soils and water ( Johnson et al, 2017 ; Wang et al, 2017 ). Even with P additions communities seemed to remain partially reliant on Solirubrobacteriaceae taxa.…”
Section: Discussionmentioning
confidence: 99%
“…For example, halotolerant bacteria associated with hydrocarbon oxidation, fermentation, and sulfur-cycling metabolisms including the genera Halanaerobium , Halomonas , Vibrio , Halolactibacillus , Marinobacter , and autotrophs belonging to Arcobacter comprise >90% of the microbial communities within flowback and produced fluids 39 . Moreover, recent studies have indicated that streams within proximity to fracking activities have undergone shifts in their bacterial community structure 35 . For example, Methylocystacea, Acetobacteraceae, Phenylobacterium , and Acidobacteriaceae and an increase in methanotrophic bacteria abundance were linked to Marcellus shale activity 40 .…”
Section: Introductionmentioning
confidence: 99%